Economic indicators of lapse rate in the life insurance Industry / Hendon Redzuan (Faculty of Business and Management ; UiTM Press, 2006)
This paper adopts the conceptual approach which summarizes the findings of previous studies related to life insurance lapse rate. Based on the research under reviewed, several economic indicators have been hypothesized to influence the lapse rate behavior in the life insurance industry. Among the major economic factors identified are the interest rate, unemployment rate, inflation rate and level of income. The interest rate is consistently demonstrated to have significant effect on the lapse rate in the long-run. On the other hand, unemployment rate is shown to influence the lapse rate both in the short-run and long-run. Inflation rate is shown to have detrimental effect on the life insurance industry growth, while income is contended to improve life insurance policy retention.